Genetic characterization and phylogenetic analysis of skunk-associated rabies viruses in North America with special emphasis on the central plains - Davis, Rolan D.; Nadin-Davis, Susan A.; Moore, Michael C.; Hanlon, Cathleen A. (My University, 2013)
Across North America the skunk acts as a reservoir for several rabies virus variants. Some of these variants are geographically restricted in range as is the case for the California skunk variant and two distinct variants present in Mexico. In contrast the North Central and South Central skunk rabies viruses are dispersed in overlapping ranges over large areas of the Midwestern region of the United States with the former extending into southern parts of the Canadian prairies. Despite this extensive range, there has been only very limited molecular characterization of these two viral variants. This study has examined the genetic diversity of the rabies viruses associated with North American skunks, with particular emphasis on the South Central skunk variant which was found to comprise three distinct geographically restricted groups of viruses that could in some cases be further sub-divided. The phylogenetic relationships of these groups and sub-groups allowed us to infer the likely direction of spread of these variants in some instances. Patterns of amino acid replacement of North American skunk-associated rabies viruses for both the nucleoprotein and glycoprotein products are also examined. These patterns reflect the virus phylogeny but no amino acid residues associated specifically with the skunk host were identified.
Keywords: Rabies virus; Phylogeography; Phylogeny; Nucleoprotein; Glycoprotein